THE STYLES OF JAVANESE POLITICAL LEADERSHIP IN PRAMOEDYA ANANTA TOER’S NOVEL AROK DEDES - Yuhandri Pane; M. Manugeren; Purwarno Purwarno (JOURNAL OF LANGUAGE, 2021)
The research is focused on the styles of Javanese political leadership revealed in the novel Arok Dedes written by Pramoedya Ananta Toer. The Javanese leadership style is a cultural heritage and deserves to be maintained and revitalized and to be adjusted to the changing of times. Javanese people live side by side in harmony with cultural norms and values  and lifestyle becomes an ethnic identity.  The objectives are to find styles and how the styles of Javanese political leadership are revealed in Pramoedya Ananta Toer’s novel Arok Dedes. A theory of Javanese leadership style, with its slogan of 5Ms is used a base and the whole research is conducted by means of descriptive qualitative method revealing the individual personality. The results show that the 5Ms of style are found in the novel: 1) melek/awas (awareness), 2) melik (sense of ownership), 3) muluk (poverty solution, 4) melok (aspiration realization), and 5) meluk (accomodation), all of which are performed by a leader of Tumapel district, named Ken Arok.